Comparative effects of open-skill and closed-skill sports on executive function in university students: a 16-week quasi-experimental study - Li, Y.-F.; Gao, T.; Luo, L.-P.; He, S. (Frontiers in Psychology, 2024)
Introduction: Previous reviews have often concluded that open-skill sports are more effective at enhancing executive function (EF) than closed-skill sports. However, this conclusion may not hold for closed-skill sports with high cognitive demands, such as golf. This study aimed to compare the effects of football (open-skill) and golf (closed-skill) training on enhancing EF in university students.